Health Promotion and Related Factors Among Korean Goose Mothers - Chiyoung Cha, PhD, RN (Elsevier, 2010)
The purpose of this study was to further understand the health promotion behaviors of Korean goose mothers in the North America area. Health promotion behaviors measured in this study were self-actualization, health responsibility, physical activity, nutrition, interpersonal relations, and stress management. Methods: The study is part of a larger study which used surveys (N=140) and in-person interviews (n=18). In this study, analysis of survey results is presented. Advertisements and snowballing technique were used to recruit study participants. Pearson's correlation was used to explore the relationships between health promotion and social support, acculturation attitudes, and perceived family health. Multiple regressions were used to examine the predictors of health promotion behaviors. Results: Women in the study were most frequently engaging in self-actualization and least in physical activity. Physical activity did not correlate with any of the study variables. When multiple regressions were performed, the model for each health promotion behavior was found to be statistically significant except for that of physical activity. Overall, study variables worked differently across models. Social support predicted self-actualization, health responsibility, interpersonal relations, and stress management. None of the acculturation attitudes predicted health promotion behaviors. The subdimensions of perceived family health predicted health promotion behaviors except physical activity. Conclusions: The findings of this study contributed to the body of knowledge of health promotion among international migrant populations by identifying the differential effects of social support, acculturation attitudes, and perceived family health for six areas of health promotion.